Analisis Pengaruh Promosi dan Kualitas Pelayanan Terhadap Minat Menabung di Bmt Syariah Riyal KCP Karang Satria Kabupaten Bekasi - Reni Yesi; Harliana (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
BMT Syariah Riyal is a sharia-based microfinance institution. BMT Syariah Riyal has a legal entity as a sharia financing savings and loan cooperative. The purpose of this study was to find out how much influence promotion and service quality have on the intention to save at BMT Syariah Riyal at KCP Karang Satria, Bekasi Regency. The author uses data collection methods in the form of library research and questionnaires. Instrument trials include validity tests and profitability tests. This test also uses classic assumption tests which include normality tests, multicollinearity tests and heteroscedasticity tests. The data analysis technique used is multiple linear regression. The hypothesis test uses the goodness of fit test which includes the coefficient of determination test (R2), t test (partial) and F test (simultaneous). Based on the calculation of multiple linear regression analysis, the value of Y = 3.095 + 0.845X1 + 0.217X2 is obtained. From these results it can be concluded that the promotion variable (X1) has a greater interest in saving by 0.845. Then followed by the service quality variable (X2) which is equal to 0.217. The results of the test for the coefficient of determination (R2) obtained a result of 64.7% while 35.3% was influenced by other variables. The results of the promotion t-test hypothesis test have a calculated t value > from t table, namely 5.306 > 2.011. It can be concluded that there is a positive and significant influence between the promotion variables on the intention to save. And service quality has a t count > from t table, which is 2.020 > 2.011. It can be concluded that there is a positive and significant influence between service quality variables on the intention to save. Based on the calculation results of the F Test (simultaneous) the value of F count > F table is 45.887 > 3.20. So, it can be concluded that there is a significant influence between the promotion variable and service quality on the intention to save.